Neuromodulatory effect of zerumbone on alpha-2A adrenoceptor, NMDA N2B receptor and TRPV1 channel in LPS-induced SH-SY5Y cells, a neuropathic pain-like in vitro model - Mohammed Izham, Noor Aishah (2021)
Refer to PDF